Hubungan Pengetahuan dan Sikap Terhadap Perilaku Pencegahan Infeksi Saluran Pernapasan Akut (ISPA) Pada Driver Ojek Online - Maria Liska Ledwina Koma; Maria Lousiana S. (Jurnal Kesehatan Saelmakers PERDANA (JKSP), 2021)
Air pollution in Jakarta increase every year which cause health problems. The quality of Jakarta's air with the status of very unhealthy develop various type of diseases, such as Acute Respiratory Infection (ARI). ARI is an infection that attacks one or more parts of the respiratory tract starting from the nose to the alveoli including (sinus, ear cavity, and pleura), the limit of this acute infection lasts up to 14 days, although generally for several diseases that can be classified as in ARI it can last more than 14 days. This study aims to determine the relationship between level of knowledge and attitude to prevention behavior of acute respiratory infections (ARI) on online motorcycle drivers at DKI Jakarta region. This study was a quantitative research with a descriptive correlative research design using cross sectional approach and questionnaires were given through Google Forms for instruments in this study. There were 106 online motorcycle drivers chosen using random sampling technique. The results revealed that most respondents had good level of knowledge (82.1%), positive attitude (74.5%), and good preventive behavior (60.4%). Using Kendall Tau C statistical test declared that there was no significant relationship between knowledge and prevention behavior of ARI (p-value = 0.080) and using Kendall Tau B statistical test shows a significant relationship between attitudes with ARI prevention behavior (p-value 0.019). It is suggested that health workers provide health education to the community, especially online motorcycle drivers with more focus on the impact, etiology, and transmission of ARI, thus, it will build good community behavior of ARI prevention.